A history of collection development at the Suter Art Gallery, Nelson, 1896-1997 : a dissertation presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Massey University - Taylor, Judith M. (Massey University, 1997)
The dissertation outlines the history of the collection at the Suter Art Gallery and traces patterns of collecting and collection growth there. The broader New Zealand historical, sociological and museological context of the collection is considered and discussed with reference to literature on collecting in other New Zealand institutions. The influence of shifting cultural fields and their effect on collecting at the Suter Art Gallery is considered. Reassessment of the collection and changes in collecting practices at the Gallery are examined with reference to specific events and influences. The extent to which the collection is representative of the growth and development of the arts and artistic production in the Nelson Region is discussed. Unique characteristics of the collection are identified and discussed. Possible directions for the future of collecting at the Gallery are outlined.
Keywords: Bishop Suter Art Gallery; Art museums; New Zealand; Nelson; Acquisitions; Management; Art museums